The Impact of School Finance Litigation - David C. Thompson; Faith E. Crampton (Educational Considerations, 2000)
School finance litigation has been a hot topic for more than three decades. Starting in the 1960s, school districts began bringing suit in federal and state courts in an effort to force greater fairness in funding for schoolchildren.